French discourse analysis in the organization of information and knowledge in Brazil: Epistemological considerations to documentary analysis - Carvalho, Marcos Vin-Cius Santos [UNESP]; Almeida, Carlos C-Ndido [UNESP]; Sabbag, Deise Maria Antonio [UNESP] (Universidade Estadual de Campinas, 2019)
It investigates how the Information Science in Brazil establishes its interdisciplinary dynamics with the French Discourse Analysis, which has unfolded in different theoretical and methodological orders. In addition, it analyzes, from a diachronic perspective, the epistemological interactions between the French aspect of Discourse Analysis and Information Science, especially with regard to the Organization of Information and Knowledge. Through a literature review, it shows the main historical contributions of discourse theory to the informational field in the Brazilian context. Among the theoretical contributions of Discourse Analysis is the The article explores the dialogical relationship that can be established between the French theory of discourse analysis in the Information and Knowledge Organization in the Brazilian context. In the broad sense, the reflective path comprises a possible gnosiology present in the Science of Information and the discursive studies. The focus of this analytical study is on the interdisciplinary issues, as well as on the epistemological relationships, that this dialogue presents for Documentary Analysis. The objective is to establish the interdisciplinary relations of the two areas of study in the Brazilian context, having as a methodological path for the understanding of this diachronic perspective the critical epistemology. Three lines of discourse analysis were chosen for the purpose of the dialogical relationship: the line of Michel P-cheux, the line of Sociolinguistics and the line of Michel Foucault. The first and third are present in works carried out in the field of Information Science, especially in the convergences with Documentary Analysis, having as confluence information as discourse, subject, language and pragmatics. Possible paths point to a scenario affected by power disputes. Thus, this scenario produces meaning effects and needs to be analyzed by a reading gesture, taking into account the historical issues of time and space, because depending on the cultural and temporal moment, information and discourse can produce different effects of meaning.
Keywords: Epistemology; Information Science; Interdisciplinarity; Organization of Knowledge